Bio-based semi-crystalline PEF: Temperature dependence of the constrained amorphous interphase and amorphous chain mobility in relation to crystallization. (28th April 2022) - Righetti, Maria Cristina; Vannini, Micaela; Celli, Annamaria; Cangialosi, Daniele; Marega, Carla
Abstract: The temperature dependence of the constrained amorphous interphase or rigid amorphous fraction (RAF) in bio-based semi-crystalline poly(ethylene 2, 5-furandicarboxylate) (PEF) was assessed. RAF, which is located in proximity of the basal crystal planes, was found to develop in parallel with the crystal phase during crystallization at the lowest investigated Tc s, i.e. 130 and 140 °C, at which the less stable α′-crystal phase grows. At higher Tc s, RAF does not vitrify during crystallization, but only upon the subsequent cooling down to Tg . The rigid amorphous fraction at Tg increases by decreasing the crystallization temperature, ranging approximately from 15 to 25%. This information is useful for the development of PEF products, since many RAF physical properties, for example mechanical and barrier properties, are different from those of the amorphous fraction far from the crystals. RAF decreases with increasing temperature, and becomes zero around 150 °C. The same temperature limit of 150 °C was found to influence the reversing crystallization/melting process at the lateral crystal surfaces, as well as the crystallization rate, which reaches its maximum at temperatures above 150 °C. In addition, singularly, the more ordered crystalline α-form was found to grow only at temperatures higher than 150 °C. The total absence of constraints on the amorphous segments mobility, identified at temperatures higher than 150 °C, also favors additional crystallization upon heating in the PEF samples crystallized at low T c s, with also α-crystals development. The densities of the RAF connected to α′- and α-crystals were estimated at room temperature. Graphical abstract: Image 1 Highlights: The temperature dependence of the rigid amorphous fraction (RAF) of the bio-based PEF has been quantified. The RAF at Tg ranges from 15 to 25% and increases by decreasing T c . The RAF decreases with increasing temperature, and becomes zero around 150 °C. The more ordered crystalline α-form grows only at temperatures higher than 150 °C. The densities at T room of the RAF connected to α′- and α-crystals are lower than that of the MAF.